Analisis Strategi Go To Market Apple Vision Pro melalui pendekatan Integrated Marketing Communication - Maulana, Akmal; Mansoor, Alvanov Zpalanzani (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2025)
This study aims to analyze the Go-To-Market (GTM) strategy and the use of Integrated Marketing Communication (IMC) by Apple in the launch of the Apple Vision Pro product. Employing a qualitative approach, this research evaluates various aspects of Apple's IMC campaign, including advertising, sales promotion, public relations, personal selling, and direct marketing. The findings indicate that the effective integration of various marketing communication elements plays a key role in achieving commercial success for the product. The synergy between innovative advertising campaigns, personalization in sales promotion, and strong public relations strategies has successfully created enthusiasm and enhanced product awareness. This study provides insights on how strategic adaptation to new trends and technologies can optimize product launches in highly competitive markets. Recommendations for further research include exploring the long-term impact of IMC strategies, conducting comparative studies with competitors, and utilizing quantitative data to more objectively measure campaign effectiveness.